1.5% Glycine vs 5% Glucose Irrigant During TURP on Serum Electrolytes & TUR Syndrome” Which One is Better? (Bangladesh Journal of Urology, 2022)
Objective: To observe the changes in the serum electrolytes and occurence of the transurethral resection syndrome (TUR) with 1.5% glycine and 5% glucose as an irrigant fluid during TUPRPatients and methods: Between June 2008 and May 2010, 120 patients were included in a prospective comparative trial comparing 1.5% glycine with 5% glucose irrigation fluids. We measured blood loss, fluid absorption, biochemistry including serum electrolytes RBS and peri-operative symptoms. Blood samples were taken before and immediately and 24 h after TURP. Irrigating fluid absorption during TURP was measured by serum sodium level. Operative details were recorded, including the type of anaesthesia (with or with no sedation), resection time and weight of resected tissue. Peri-operative symptoms were documented prospectively. TUR syndrome was defined as a serum sodium level of £125 mmol/L with two or more associated symptoms or signs of TUR syndrome.Results: Two (1.67%) patients had TUR syndrome; all two were irrigated with glycine, although this difference was not statistically significant (P = 0.10). Of the two patients who had TUR syndrome, one had bradycardia, two had hypotension, two were drowsy, one was nauseous, two had prickling sensation, two experienced uneasiness, one had blurred vision and two were confused; none had chest pain. There was no difference between the groups in levels of sodium, potassium, urea, creatinine or peri-operative blood loss (defined as a change from before to after TURP in haemoglobin level, accounting for transfusions).Conclusions: Endoscopic transurethral resection of the prostate performed using 5% glucose as irrigating solution during surgery, when compared with 1.5% glycine are associated with lower perioperative morbidity including TUR syndrome. Except for the transient postoperative hyperglycemia, in glucose group, both irrigants are nearly equivalent & safe. In other studies, glycine was reportedly toxic, and that the levels recorded were many times the upper limit of normal may have both immediate and long-term effectsBangladesh J. Urol. 2021; 24(1): 9-13